Peri-urbanisation, counter-urbanisation, and an extension of residential exposure to ticks: a clue to the trends in Lyme borreliosis incidence in the Czech Republic? - Zeman, Petr; Benes, Cestmir (Ticks and tick-borne diseases, 2014)
The incidence of tick-borne human diseases (TBD) in the Czech Republic (CZ) is on the increase, driven by infections increasingly acquired in residential locations, earlier in spring and later in autumn, and among children and the elderly. To interpret these trends, data on Lyme borreliosis (LB) incidence between 1997 and 2010 were analysed in the context of population migration flows registered in the CZ during the same period. Analysis showed that a migration stream of families with children, and of the elderly, flowed from more urbanized and densely populated localities to those more rural and less populated, where the chance of acquiring LB in the home vicinity was greater than in the urban settings. By contrast, a stream of people in the life phase between early adulthood and family formation flowed reversely, corresponding to a prominent absence of this age category from the patient spectrum. The data further showed that the more the residential exposure became prevalent, the more people were in year-round (rather than in summertime only) contact with ticks, which accounts for an extension of the cases' seasonal distribution as well as for an overall increase in case numbers. Finally, the fact that majority of the urban-to-rural migrants could be categorised as wealthier people could explain the previously noticed lack of low-status people among TBD patients in the CZ.
Keywords: lymeská nemoc; dospělí; Animals; Female; Seasons; Infant; Counter-urbanisation; Tick-Borne Diseases; dítě; předškolní dítě; Urban Population; Adult; ženské pohlaví; mladý dospělý; Adolescent; lidé; Suburbanisation; nemoci přenášené klíšťaty; roční období; Aged, 80 and over; Humans; Incidence; klíšťata; Ticks; venkovské obyvatelstvo; Male; Disease emergence; incidence; kojenec; Aged; Czech Republic; Lyme borreliosis; Child, Preschool; městské obyvatelstvo; Lyme Disease; Young Adult; Amenity migrants; Česká republika; lidé středního věku; Child; senioři nad 80 let; senioři; zvířata; mužské pohlaví; Middle Aged; mladiství; Rural Population; Borrelia